Travelling-Wave Similarity Solution for Gravity-Driven Rivulet of a Non-Newtonian Fluid - Sabariah Abas, Siti; Mohd Yatim, Yazariah; ., . (International Journal of Engineering and Technology, 2018)
Unsteady travelling-wave similarity solution describing the flow of a slender symmetric rivulet of non-Newtonian power-law fluid down an inclined plane is obtained. The flow is driven by gravity with strong surface-tension effect. The solution predicts that at any time  and position , the rivulet widens or narrows according to , where  is velocity of a rivulet, and the film thickens or thins according to a free parameter , independent of power-law index . The rivulet also has a quartic transverse profile which always has a global maximum at its symmetrical axis.